Kidung Koplo as a Media for Preserving Javanese Language for the Millennial Generation of Javanese Diaspora in South Sumatera - Rohmawati, Yulia; Mumtaz, Rafida; Azzah, Iftifaroh; Khusyairi, Johny Alfian (Universitas Airlangga, 2023)
This article aims to examine the use of Javanese dangdut koplo music and Kidung Koplo podcast as alternative media for preserving Javanese language among the millennial generation of Javanese diaspora in South Sumatra. Javanese dangdut koplo is very popular among the millennial generation throughout Indonesia. On the other hand, podcast is also considered as a very high popularity trend among the millennial generation. Hence, the use of Javanese dangdut koplo music and podcasts is assumed to be a potential alternative media in preserving Javanese language. To pursue the aim of this article, a qualitative-descriptive approach was used. To collect data, interviews, observations, and literature study then were conducted. The primary sources in this article were language and culture experts; the history of dangdut koplo music development; dangdung koplo singers; as well as the millennials of Javanese diaspora in South Sumatra. The results showed that Kidung Koplo podcasts presenting dangdut songs with translations and meanings were able to increase understanding and insight of the millennials into Javanese language still poorly mastered. In conclusion, digital media that is popular among young people can be used as a means of education and preservation, therefore, podcasts then can increase the interest and ability of millennials to understand new knowledge, in this case Javanese.